The Politics of State Creation in Nigeria and the Economic Viability of the Existing 36 States - Onimisi, Timothy (International Journal of Social Sciences and Management, 2014)
The politics of state creation in Nigeria has assumed a worrisome dimension. The demand for creation of new states is growing in an unfortunate manner, political and ethnic associations are at their best to undo one another a head of the 2014 National Conference. The attention of scholars has being drawn to the continuous demand of some leaders agitating for new states considering he weak economic viability of most of the existing states and a near bankrupt of most of the states judging from the indicators and index of the economic agencies in Nigeria. This paper attempt to bring out a clearer economic viability of the existing states and it intend to call on those seeking for more states to cease, judging from the economic situation of the existing states and their total dependence on the central government for survival. The paper recommends the need to reposition and strengthen the existing 36 states structure, and it call on the people of Nigeria to support the Federal government in her attempt to transform the states. DOI: http://dx.doi.org/10.3126/ijssm.v1i2.10009 Int. J. Soc. Sci. Manage. Vol-1, issue-2: 64-68